PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTs. SWASTA AL-IKHLAS KEBUN AJAMU KECAMATAN PANAI HULU KAB. LABUHANBATU - Nurul Fadillah (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to describe the leadership: the role of the head of the madrasa in improving the quality of education in Private MTS. Al-Ikhlas Gardens Ajamu Labuhan Batu Regency Panai Hulu Subdistrict. The approach in this research is descriptive analysis approach. As informants in this study is the head of the madrasa, Deputy Head of the madrasa curriculum areas, officials of the Administration, teachers, students. Data collection techniques used in this research is the interview, observation and documentation. Data analysis was performed by means of the reduction of the data, the presentation of data, and the withdrawal of the conclusion. While testing the validity of the data is done by way of credibilitas, transferabilitas, dependabilitas, and confirmabilita. The findings of this research show that: 1) head of the madrasa has done well in accordance with his leadership role and functions as head of the madrasa. 2) the quality of education in Private MTS. Al-Ikhlas Ajamu Gardens already meet 8 education standards (SNP). 3) leadership roles of the head of the madrasa in improving the quality of education in Private MTS. Al-Ikhlas Gardens Ajamu, namely: As edukator, manager, administator, supervisor, leader, innovator, motivator. A leadership role in improving the quality of head of the madrasa is done by: a) lays out the vision into mission to achieve the target of quality, b) head of the madrasa formulate objectives and targets will be achieved, quality c) Analyse the challenges, opportunities, strengths and the weakness of the madrasa, d) in making the decision the budget discussion with the head of the madrasa Islamic party foundations, e) Involving the Board of teachers and administrative decision-making in important madrasa, f) Provide and increase the motivation of working educators and educational personnel. 4) inhibitor Factor towards improved quality of education in Private MTS. Al-Ikhlas Ajamu Gardens. Includes internal and external factors. That included internal factors are funds/financial madrasah, while the included external factors is the territory of the community and the environmentKeywords: Leadership Of The Head Of The Madrasa, The Quality Of Education